2015
DOI: 10.1589/jpts.27.3901
|View full text |Cite
|
Sign up to set email alerts
|

The effects of non-elastic taping on muscle tone in stroke patients: a pilot study

Abstract: [Purpose] Hemiplegia occurs when posturing with a dominant flexor tone is present in the upper limbs, thus preventing increased abnormal tone. We attempted to improve the side effects of this condition using elbow re-positioning with non-elastic tape; this method is used to modulate abnormal muscle tone in chronic hemiplegic stroke patients. [Subjects and Methods] Fourteen post-stroke patients were included in this study. Non-elastic tape was applied to the elbow joint in a spiral manner. Before and after the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The mechanical properties of muscles such as tone, elasticity, and stiffness are often affected in patients with stroke [ 1 ]. Muscle tone is considered to be fundamental in maintaining balance, posture stability, and energy efficient muscle contractions [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties of muscles such as tone, elasticity, and stiffness are often affected in patients with stroke [ 1 ]. Muscle tone is considered to be fundamental in maintaining balance, posture stability, and energy efficient muscle contractions [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stroke involves rapid loss of brain function resulting from a disturbance in the blood supply to the brain; it often profoundly affects upper limb stability and movement capacity. Stroke is the third leading cause of death worldwide, and it is the leading cause of severe disability in patients in the developed world 1 , 2 , 3 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have applied this technique to post-stroke. Kim et al, showed that this kind of tape could be used to decrease elbow flexor tone (26). Kilbreath et al recommended that gluteal taping has an immediate effect on enhancing in the hip extension during stance phase in stroke subjects (27).…”
Section: Discussionmentioning
confidence: 99%